THE INFLUENCE OF INFLATION RATE, INTEREST RATE, AND MONEY SUPPLY ON SHARE PRICE LQ45 - Gursida, Hari (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
The purpose of this study is to determine the influence of inflation rate, interest rate, and money supply on LQ45 stock price either partially or simultaneously. This research is a quantitative research that aims to test the hypothesis. Objects in this study are: inflation rate, interest rate, money supply, and stock price LQ45. The research period is 2010 to 2016. The data used is quantitative data from secondary sources. The method of analysis used is multiple linear regression with hypothesis testing using t test and F test. Based on the results of the study it can be concluded that: 1) the inflation rate does not affect the CSPI LQ45; 2) the interest rate does not affect the CSPI LQ45; 3) the money supply has a significant influence on CSPI LQ45; 4) Simultaneously, the inflation rate, interest rate and money supply have a significant influence on CSPI LQ45.